Polymeric nanoreactors for catalytic applications - Abou-Fayssal, Chantal Joseph; Poli, Rinaldo; Philippot, Karine; Riisager, Anders; Manoury, Eric (Comptes Rendus. Chimie)
Mimicking Nature is one drive for chemists to design efficient architectures matching the activity and selectivity of natural catalytic systems, such as enzymes. To this extent, the developed architectures need to have a selective and active site for the transformation of a given substrate to a target product. In addition, the catalyst must be recoverable and recyclable in order to improve the efficiency and be sustainable. Nature achieves these goals by embedding the catalytically active site in an adapted organic matrix that allows controlling the confinement of the catalytic site and its access by the substrate. Organic polymers allow confining diverse catalysts inside organic nanodomains, following the concept of catalytic nanoreactors. Anchoring the catalyst inside the polymer core protects it from the surrounding environment. This strategy also provides an efficient way to separate the catalyst from the products, thus permitting its recovery and recycling. This review provides an overview of unimolecular nanoreactor systems designed from macromolecular building blocks and their application in biphasic catalysis.